2013
DOI: 10.3892/or.2013.2284
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and phenotypic profiles of two Brazilian breast cancer cell lines derived from primary human tumors

Abstract: Breast cancer is the most common type of cancer among women worldwide. Research using breast cancer cell lines derived from primary tumors may provide valuable additional knowledge regarding this type of cancer. Therefore, the aim of this study was to investigate the phenotypic profiles of MACL-1 and MGSO-3, the only Brazilian breast cancer cell lines available for comparative studies. We evaluated the presence of hormone receptors, proliferation, differentiation and stem cell markers, using immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…Concerning MACL-1 and MGSO-3 breast cell lines, obtained from Brazilian patients, the percentage of CD24 + cells was about 5% and 46% respectively, corroborating with their classi cation in other study [24]. The presence of intracellular CD24 was also detected in the whole population of both cell lines, like observed in MDA-MB-231 population (Fig 2a,b).…”
Section: Resultssupporting
confidence: 87%
“…Concerning MACL-1 and MGSO-3 breast cell lines, obtained from Brazilian patients, the percentage of CD24 + cells was about 5% and 46% respectively, corroborating with their classi cation in other study [24]. The presence of intracellular CD24 was also detected in the whole population of both cell lines, like observed in MDA-MB-231 population (Fig 2a,b).…”
Section: Resultssupporting
confidence: 87%
“…Several studies have provided evidence that loss or deletion on chromosome 17p12-13 is associated with chemotherapy resistance in breast cancer, as well as esophageal, lung, liver and stomach cancer ( 1 , 2 , 5 , 7 10 ). A study performed in Brazil that investigated only two patients demonstrated loss of considerable portions of chromosomes 17, 19 and 22 ( 18 ). The findings of this previous study are consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is caused by the low levels of BRCA-2 protein in cells. This lead to the accumulation of damaged DNA in cell [8].…”
Section: Brca-1 and Brca-2mentioning
confidence: 99%
“…ILC also called as infiltrating lobular carcinoma, this carcinoma is the second most common type of breast cancer after IDC, according to American society of cancer; more than 180,000 women in US having ILC each year. This carcinoma spread to the adjacent tissues and begin in milk producing lobules which empty out in the duct that carry the milk to nipple [8].…”
Section: Invasive Lobular Carcinomamentioning
confidence: 99%